1997
DOI: 10.1046/j.1365-2141.1997.3133126.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of P2x1 purinoreceptors on rat platelets: effect of clopidogrel

Abstract: Summary. This study aimed to determine the binding characteristics of [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…Clopidogrel (Sanofi-Synthelabo, Toulouse, France) at 10 mg ⅐ kg Ϫ1 ⅐ day Ϫ1 (20), aspirin at 30 mg ⅐ kg Ϫ1 ⅐ day Ϫ1 , or sorbinil (Pfizer, Groton, CT) at 65 mg ⅐ kg Ϫ1 ⅐ day Ϫ1 (17) was given to diabetic and control rats. Clopidogrel and aspirin were incorporated into pellets of the customary grain-based rodent diet (Bio-Serv, Frenchtown, NJ) with red and green food dye, respectively, to prevent incorrect delivery of treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Clopidogrel (Sanofi-Synthelabo, Toulouse, France) at 10 mg ⅐ kg Ϫ1 ⅐ day Ϫ1 (20), aspirin at 30 mg ⅐ kg Ϫ1 ⅐ day Ϫ1 , or sorbinil (Pfizer, Groton, CT) at 65 mg ⅐ kg Ϫ1 ⅐ day Ϫ1 (17) was given to diabetic and control rats. Clopidogrel and aspirin were incorporated into pellets of the customary grain-based rodent diet (Bio-Serv, Frenchtown, NJ) with red and green food dye, respectively, to prevent incorrect delivery of treatment.…”
Section: Methodsmentioning
confidence: 99%
“…It was suggested that human platelets express a P2X1 receptor, which mediates rapid Ca 2+ entry, in contrast to the P2Y receptors which evoke release of calcium from intracellular stores [268]. Clopidogrel did not affect the binding of α,β-meATP to platelet P2X1 receptors [269]. The P2X1 receptor cDNA and protein was identified on human platelets, but not leukocytes [270][271][272].…”
Section: P2x1 Receptorsmentioning
confidence: 99%
“…The latter is the target for specific antithrombotic drugs (reviewed by Gachet 7 ). Platelets express the P2X 1 member of the P2X family of ligand-gated ion channels, 8 which mediates a rapid ATP-induced Ca 2ϩ influx. 9,10 Because of the fast desensitizing property of the P2X 1 ion channel 11 and the lack of specific platelet P2X 1 antagonists and because platelet studies have mainly been performed ex vivo at low extracellular Ca 2ϩ concentrations in citrated plasma, the function of P2X 1 in platelet activation only recently started to be unraveled, and a physiologic role of ATP in this process is now being considered.…”
Section: Introductionmentioning
confidence: 99%